Conselho escolar : instrumento de gestão democrática ou autoritarismo velado? - Soares, Gilson Lopes (2016)
The present work is inscribed in the search line Social Movements, Policies and Popular Education of the Program of Post graduation in Education, of the Federal University of Mato Grosso. It has, as analysis object, the school councils of three state schools in the city of Ji- Paraná – Rondônia. This process is circumscribed in the context of the Brazilian State Reform, what it was carried out in the middle of the years of 1990, and the educative reforms resulting from the reconfiguration process of the education to the new market determinations, and the educators’ resistance and popular movements to the effectuation of these propositions. The school councils in Rondônia are still a new reality, however, from the year of 2011, his short history gives us necessary elements for a depth analysis of the lived reality in the investigated schools. Same they still constitute antidemocratic arrangements in the institutions, perpetuating a hierarchical management; even if there the “permission” for the participation, there are no propitiating conditions of this participation, since the State gives to the directors an authoritarian character, from which emanate all the orders in the institution. For that, there are defined as guiding objectives: thinks about the democratic school management prioritized about the education directives, highlighting the legal marks: Federal Constitution of 1988, Law n. 9.394/96 – Law of Directives and Bases of the National Education (LDB), and the Law n. 3.018/2013, from the State of Rondônia, which provides for the democratic management, with purpose of analyzing the paper of the school councils. As for the used methodology, the present study is characterized like a qualitative inquiry, which methodological proposal was developed articulating documentary and empirical inquiry. It was looked that theoretical support in the contributions of Paro (1999, 2000, 2001, 2007, 2008, 2010, 2011, 2012 e 2015), Libâneo (2003, 2013), Gohn (2011, 20013) and Silva (2008), between others. In the data collection was used analyses of the minutes books of the councils, of the pedagogic political projects. We still use the questionnaire applied to the titular counselors of each council. Besides, interviews were still carried out with 5 (five) titular counselors of each council, besides checked the speech of 4 (four) members of the school community (parents, teachers, pupils, employees) of three no council members schools. Through the fulfilled study, it is possible to check that the democratic management of the school is distant from constituting a reality that, effectively, could contribute to alter the relations of power in the school inside, so, even then elections are for provision to the post of school director, as well as legally constituted School Councils, the hierarchy of relations as not altered; the community participation in the education subjects limited itself to opinion or hunches, when consulted, and the acting from the members of the SC served to legitimize the manager action which uses it to ratify the antidemocratic practice within the institutions. The impeditive ones to the full effectuation of SCs can be identified by the managerial and business perspective what the institutions adopt, which deny the political character, so perpetuating clientelistic practices endorsed by the current societal project. We believe that this dissertation can offer subsidies to the discussion with regards to the democratic management in the public state schools in the city of Ji-Paraná, contributing to have a planning of the actions, in the perspective of a bigger knowledge by the school community on the conception of the democratic management principles, autonomy and participation, in order to contribute to the overcoming of the social contradictions that have repercussions on the interior of the schools, with sights to the emancipator process of the student, essentially for the construction of a most human and democratic society.